![](https://blog.hocmai.vn/wp-content/uploads/2017/07/hot.gif)
![](https://blog.hocmai.vn/wp-content/uploads/2017/07/hot.gif)
Cho 2 đa thức sau :
A (x) = [tex]x^{3}-3x^{2}+6x-8[/tex]
B (x) = [tex]-6x^{2}+x^{3}-8+12x[/tex]
Tìm x để A (x) = B (x)
@besttoanvatlyzxz @Đoan Nhi427 @huythong1711.hust @iceghost @Ann Lee @quynhphamdq @Blue Plus @hdiemht
A (x) = [tex]x^{3}-3x^{2}+6x-8[/tex]
B (x) = [tex]-6x^{2}+x^{3}-8+12x[/tex]
Tìm x để A (x) = B (x)
@besttoanvatlyzxz @Đoan Nhi427 @huythong1711.hust @iceghost @Ann Lee @quynhphamdq @Blue Plus @hdiemht